2017
DOI: 10.1186/s12879-017-2619-y
|View full text |Cite
|
Sign up to set email alerts
|

Age-standardized mortality rates related to viral hepatitis in Brazil

Abstract: Background: Liver-related mortality has been increasing worldwide. We aimed to estimate the age-standardized mortality rates from viral hepatitis in Brazil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 34 publications
1
4
0
3
Order By: Relevance
“…We found that overall survival was worse for those with HCV than those with HBV; 12.2% of the cohort with HCV died vs 3.2% of those with HBV. The crude risk of death was 4 times higher for those with HCV than HBV, and 2 times higher after adjustment, consistent with findings from other studies [ 21 ] and with our previous findings on survival specifically among individuals with HCC [ 17 ]. Individuals with HCV were also 3.2 times more likely to be diagnosed with HIV and 17% more likely to be diagnosed with HCC than those with HBV, even after adjusting for other factors that might have affected these diagnoses.…”
Section: Discussionsupporting
confidence: 91%
“…We found that overall survival was worse for those with HCV than those with HBV; 12.2% of the cohort with HCV died vs 3.2% of those with HBV. The crude risk of death was 4 times higher for those with HCV than HBV, and 2 times higher after adjustment, consistent with findings from other studies [ 21 ] and with our previous findings on survival specifically among individuals with HCC [ 17 ]. Individuals with HCV were also 3.2 times more likely to be diagnosed with HIV and 17% more likely to be diagnosed with HCC than those with HBV, even after adjusting for other factors that might have affected these diagnoses.…”
Section: Discussionsupporting
confidence: 91%
“…In total, 59 epidemiological articles were included (Table 1). An additional article was found that presented data on hepatitis A mortality [20]. Since hepatitis A infection is rarely fatal and its burden is usually related to its morbidity [21], this article was excluded from further analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Between 1999 and 2015, HAV infection comprised 31% of all viral hepatitis reported in Brazil, with the North and Northeast regions accounting for 57% of all confirmed cases of hepatitis A and presenting the highest age-standardized mortality rate [6,7]. Since 2006, the overall incidence rate of HAV infection in Brazil has shown a downward trend, from 9.1/1,000,000 inhabitants to 3.1/1,000,000 in 2013 [7].…”
Section: Introductionmentioning
confidence: 99%